SOIL SLOPE REINFORCEMENT USING CANTILEVER RETAINING WALL ON THE WEST RING ROAD OF SADAWARNA DAM, SUBANG DISTRICT - Rizki, Afdal; Alam, Boy Yoseph Cahya Sunan Sakti Syah; Khoirullah, Nur; Sophian, Raden Irvan; Firmansyah, Yusi (Journal of Geological Sciences and Applied Geology, 2023)
The research was conducted in the West Ring Road of Sadawarna Dam, Subang Regency. This research aims to provide recommendations for the design of cantilever retaining wall to increase the value of the slope safety factor in the research area. Calculation of the value of the slope safety factor uses the limit equilibrium method with the Janbu calculation method. In actual conditions, the value of the slope safety factor shows an unstable value referring to SNI 8460:2017, namely in static conditions with a vehicle load is 1.31 and in pseudostatic conditions with a vehicle load is 1.083. Slope strengthening was carried out using cantilever retaining wall. The retaining wall design that has been made meets the criteria for stability against overturning, stability against sliding, and stability for the bearing capacity of the soil. The safety factor value for slope with retaining wall shows a stable FS value referring to SNI 8460:2017, namely 1.53 in static conditions with vehicle loads and 1.11 in pseudostatic conditions with vehicle loads. Keyword: slope, safety factor, retaining wall, cantilever